(Re)Integrating spirituality into higher education - Salleh, Arfah; Kumar, Naresh; Ahmad, Aziuddin (2009)
This article examines the issue of accountability and governance among higher learning institutions in discharging their duties to inculcate good behaviour and mould their graduates into human business leaders. In order to appreciate the role of higher education and the requirement of the market place for graduates, we go backward in origin into the past to learn the education philosophy that has shaped today's vocation. The distinctiveness of this article is that we review the advances in the science of quantum physics to understand the current worldview of reality. The way forward for higher learning institution to reintegrate spirituality in molding young generation who actualize authentic leadership and rightness-of-action founded upon the interconnectedness model of the universe is deliberated.